Bulks of Al-B-C obtained by reactively spark plasma sintering and impact properties by Split Hopkinson Pressure Bar - Vasylkiv, O. (2021)
Mixtures of B4C, α-AlB12 and B powders were reactively spark plasma sintered at 1800 °C. Crystalline and amorphous boron powders were used. Samples were tested for their impact behavior by the Split Hopkinson Pressure Bar method. When the ratio R = B4C/α-AlB12 ≥ 1.3 for a constant B-amount, the major phase in the samples was the orthorhombic AlB24C4, and when R < 1 the amount of AlB24C4 significantly decreased. Predictions that AlB24C4 has the best mechanical impact properties since it is the most compact and close to the ideal cubic packing among the Al-B-C phases containing B12-type icosahedra were partially confirmed. Namely, the highest values of the Vickers hardness (32.4 GPa), dynamic strength (1323 MPa), strain and toughness were determined for the samples with R = 1.3, i.e., for the samples with a high amount of AlB24C4. However, the existence of a maximum, detectable especially in the dynamic strength vs. R, indicated the additional influence of the phases and the composite’s microstructure in the samples. The type of boron does not influence the dependencies of the indicated mechanical parameters with R, but the curves are shifted to slightly higher values for the samples in which amorphous boron was used.